Python as a key for Data Science - Gaurav,; Sindhu, Ritu (International Journal of Computer Sciences and Engineering, 2025)
Data science is the science of studying scientific data, business data and it’s an integration of Artificial Intelligence, statistics, computing technology. Data science is a field that relates to data cleansing, preparation and analysis. Data science algorithms are used in many industries like Internet searches, Digital Advertisements, Travelling, Healthcare, Gaming, Financial services etc. Data science can solve the problems like classification, identifying anomalies, to quantify, finding way of organization, decision making issues etc. In this paper, we have shown how python is useful and acts as a key to solve such problems. In addition to python, there are also some other platforms which are used to solve a task completely based on data science. Here we have focused on python and it’s packages that are highly useful for data science based problems. We have shown how python can be used for data analysis and data visualization.